The relationship between patellar volume and trochlear volume in patients with patellofemoral instability. Issue 4 (April 2022) - Ormeci, T.; Sen, S.; Turkten, I.; Gulabi, D.; Avcı, C.C.; Sakul, B.U.
Abstract : AIM: To investigate a possible relationship between both the volume and morphology of the patella and the volume of the trochlea in trochlear dysplasia (TD). MATERIALS AND METHODS: Eighteen patients with TD and 18 controls were evaluated retrospectively in two groups using computed tomography (CT). Patellar morphology was evaluated with the standard measurement methods described in the literature. Additionally trochlear sulcus volume (TV) and patellar volume (PV) were measured quantitatively using the three-dimensional volume-rendering method. The relationship between patella dimensions and volume and trochlea volume was evaluated. RESULTS: The length of the medial patellar facet (lMP), patellar width (PW), TV and PV were significantly lower in the patient group. When compared according to Dejour types, PW was statistically significantly lower than the control group in those with high-grade and those with low-grade dysplasia. A positive correlation was found between the TV and PV in both groups (patient group: r= 0.583 p= 0.011; control group: r= 0.485 p= 0.042). CONCLUSİONS: PV and the TV are related. Therefore, PV can be used as a determining parameter in the evaluation of TD. This technique can also be used for prosthesis construction and more accurate surgical planning. Highlights: The patella volume and trochlear sulcus volume are related. Patella volume can be used as a determining parameter in the evaluation of trochlear dysplasia. This technique can also be used for proper prosthesis construction and more accurate surgical planning.